Creative Media Education: Navigating Legal Challenges and the Role of Audio Engineering - Ella Elvrita (STAI Hubbulwathan Duri, 2025)
Creative media education, rooted in technology, arts, and culture, has rapidly evolved alongside globalization and technological advancement. This field includes disciplines such as audio engineering, film production, interactive animation, and the music business. This study explores two main questions: the position of creative media education within the framework of Creative Industries 5.0 and the extent to which regulatory nomenclature hinders the development of new academic programs. A normative-empirical juridical approach was adopted to analyze legal frameworks, policy challenges, and industry demands related to creative media education in Indonesia. The integration of emerging technologies, particularly Artificial Intelligence (AI), is significantly transforming creative media education. AI enables automation, enhances learning experiences, and predicts learner needs, fostering adaptability and innovation. Additionally, the field promotes diversity and inclusivity by integrating multicultural perspectives, thereby increasing its relevance to global audiences. However, rigid and outdated nomenclature in Indonesian higher education has limited institutions’ responsiveness to industry developments, creating a disconnect between academic programs and market needs. Overcoming nomenclature challenges requires active collaboration between academia and the creative sector. Proposed solutions include forging partnerships with media companies, upgrading educational infrastructure, providing hands-on learning opportunities, and reforming regulatory frameworks. These strategies aim to align curricula with industry expectations, improving graduates’ employability and problem-solving skills. To strengthen the role of creative media education in the era of Creative Industries 5.0, Indonesian higher education must embrace technological integration and reform academic structures to align with industry trends.